(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The major objective of this work was to develop once daily extended release tablets with zero order drug release for levetiracetam using wax matrix as the release retarding element. Extending drug release for highly water soluble drugs is always a challenge. In this work levetiracetam, a highly soluble drug was chosen for which extended release matrix tablets were developed using different waxes such as Compritol ATO 888, Imwitor 491, tristearin and cetylpalmitateas rate controlling materials taken in different amounts. PEG 6000 was used to regulate the availability of water inside the wax matrix and lactose was used as pore forming agent to aid the release of the drug from the wax matrix. Tablets were prepared by embedding the drug into the molten wax followed by its solidification, sieving, mixing with other excipients and finally compression. The prepared tablets were tested for hardness, tensile strength, friability, drug content and drug release studies. Type of wax, amount of wax and amount of PEG 6000 were optimized in order to achieve controlled drug release for about 24 hours. All the tablets showed good tensile strength in the range of 0.59-0.70 N/mm2, packing fraction in the range of 0.85-0.92 and friability in the range of 0.42-55% indicating their solid physical integrity. The drug release studies indicated thatthe tablets prepared with tristearin showed better control among the waxes taken. The tablets containing 150mg of tristearin, 50 mg of PEG 6000 and 50 mg of lactose showed controlled drug release for 24 h with zero-order release.